THE ROLE OF INTERNATIONAL ORGANIZATIONS IN DEVELOPING COUNTRIES - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study sought to determine the role of international organizations in developing countries, a case study of South Sudan; this was guided by four objectives which included: to ascertain the role of international organizations in development of South Sudan, to investigate the negative role of international organizations in South Sudan and to find ways in which international organizations can contribute to genuine development in South Sudan. The research was both qualitative and quantitative. It was based on both primary and secondary data. Primary data was gathered through interviews of senior government officials and questioners’ plus focus group discussions. The study was guided by two theories these included: building theory and Niccolo Machiavellis realism theory (Niccolo Machiavellis, 2000). The study concluded that Internationals organizations’ role in service delivery is more vital and a necessity to the community, it has the ability to provide its citizens with a good environment that’s safe and conducive for the community. Services such as water and sanitation, housing and health services constitute some of the main services provided by international organizations. The role of international organizations is to safeguard and provide the community adequate services that cater to every need of the residents. (Rosenbaum. A, 2013). One may argue that international organizations represent an importance of democratic principles and values that cater to the community. Among the recommendations laid down by the study include: International organizations should implement a debt collection policy that strictly deal with the debts being owed by the residents by suing defaulters who ignore the warning letters . Sithole, S. (2013) indicated that to add on international organizations should ensure a code of ethics that requires all its employees to initiate this policy by introducing incentives and transport to move around this would motivate the service provision when moving door to door and would ensure good results reducing the complaints owed by the residents to improve on service delivery, International organizations should utilize its revenue sources urgently by sourcing funds from IMF and the world bank to improve on its services, NGOs and Private Companies contributions will help councils provide more reliable and durable services that are of quality.